PENYEDIAAN FASILITAS PAPAN TULIS, MADING DAN INFORMASI UNTUK PEMBELAJARAN TATAP MUKA MASA PANDEMI DI SMA TRIGUNA 1956 - Mekar Sari Suteja; Nina Carina (PROSIDING SERINA, 2021)
The Covid-19 pandemic has also changed the pattern of learning and the quality of children's education. Many observers of the world of education inspect that the online learning system that has been implemented has caused many negative impacts such as the magnitude of the learning loss of students. This is due to the limited mastery of information technology, facilities, infrastructure, and internet access. After more than a year of a pandemic, on August 24, 2021, the government lowered the PPKM level for the Jabodetabek and Java-Bali cities from level 4 to 3. Reopen direct learning (PTM) is planned to start Monday, August 30, 2021. According to the Joint Decree of the Four Ministers, the PTM that will be implemented will consist of 2 phases, namely a transition period (2 months from the start of PTM) and new habits (after the transition period). This PKM partner, SMA Triguna, is a private high school under the Triguna Foundation which also wants to realize the PTM program in their school. However, the limited income budget is their main problem in procuring health protocol facilities such as the provision of blackboards, madding and information. The PKM implementation process is carried out through the survey stage and board prototype study; The design results review of the collaborative PKM Team with the title "Identification of Infrastructure Needs for Direct Learning System in the Pandemic Period at Triguna High School 1956"; Re-measurement in the field; material and price surveys; The submission of working drawings from partners; Looking for materials and craftsmen; The making boards process; Ended up with the handover of products from the PKM Team to Partners. It is hoped that the results of this PKM in the form of school and class information boards can increase the readiness for the implementation of the direct learning process at Triguna High School 1956.Pandemi Covid-19 juga turut merubah pola pembelajaran dan mutu pendidikan anak. Banyak pengamat dunia pendidikan melihat bahwa sistem pembelajaran daring yang selama ini diterapkan, banyak menimbulkan dampak negatif seperti besarnya learning loss peserta didik. Hal ini dikarenakan adanya keterbatasan penguasaan teknologi informasi, sarana, prasarana, dan akses internet. Setelah setahun lebih pandemik, 24 Agustus 2021 pemerintah menurunkan level PPKM wilayah Jabodetabek dan kota Jawa-Bali dari level 4 menjadi 3. Pembukaan Pembelajaran Tatap Muka (PTM) terbataspun direncanakan dimulai Senin 30 Agustus 2021. Menurut Surat Keputusan Bersama (SKB) 4 Menteri, PTM yang akan dilaksanakan akan terdiri atas 2 fase yaitu masa transisi (2 bulan sejak dimulainya PTM) dan kebiasaan baru (setelah masa transisi). Mitra PKM ini, SMA Triguna, merupakan sekolah SMA Swasta dibawah Yayasan Triguna yang turut menginginkan terealisasinya program PTM disekolah mereka. Namun, keterbatasan anggaran pendapatan menjadi permasalahan utama mereka untuk mengadakan sarana-prasarana protokol kesehatan seperti pengadaan papan tulis, madding dan informasi. Proses pelaksanaan PKM dilakukan melalui tahap survey dan studi prototype papan; review terhadap hasil desain Tim PKM kolaborasi dengan judul "Identifikasi Kebutuhan Prasarana Kegiatan Belajar Sistem Tatap Muka Masa Pandemi di SMA Triguna 1956"; pengukuran kembali di lapangan; survey material dan harga; pengajuan gambar kerja dari mitra; pencarian material dan tukang; pembuatan papan dan diakhiri dengan serah terima produk dari Tim PKM ke Mitra. Diharapkan hasil PKM berupa papan informasi sekolah dan kelas ini dapat menambah kesiapan pelaksanaan proses Pembelajaran Tatap Muka di SMA Triguna 1956.